2016
DOI: 10.3390/catal6060082
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structural Dynamics of Enzymes and Protonation States of Substrates Using Computational Tools

Abstract: This review discusses the use of molecular modeling tools, together with existing experimental findings, to provide a complete atomic-level description of enzyme dynamics and function. We focus on functionally relevant conformational dynamics of enzymes and the protonation states of substrates. The conformational fluctuations of enzymes usually play a crucial role in substrate recognition and catalysis. Protein dynamics can be altered by a tiny change in a molecular system such as different protonation states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…Elucidating the protonation states of the numerous titratable moieties in the TrpB active site at the various stages of catalysis is an active area of research . Reaction with nitrogen nucleophiles, such as indoline and 2-aminophenol, stalls the catalytic cycle of TrpS from Salmonella typhimurium ( St TrpS), enabling the structural analysis of quinonoid intermediates. These studies have indicated that proton transfer between the phenolic group of PLP and the Schiff base may occur during the catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating the protonation states of the numerous titratable moieties in the TrpB active site at the various stages of catalysis is an active area of research . Reaction with nitrogen nucleophiles, such as indoline and 2-aminophenol, stalls the catalytic cycle of TrpS from Salmonella typhimurium ( St TrpS), enabling the structural analysis of quinonoid intermediates. These studies have indicated that proton transfer between the phenolic group of PLP and the Schiff base may occur during the catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The internal motions of proteins might assist as 'gate' in some systems, which controls ligand-protein association. In many enzymes or complexes, protein motions involve an allosteric communication to coordinate the function and reactions, which could be intrinsic to most enzymes [24]. Proteins are usually functions by administered of their dynamical character.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the study of the Ni(II) bound form of SyInrS requires the development of specific force field parameters able to model a Ni(II) ion in the square planar coordination. In recent years the improvement of the computational capabilities and the development of accelerated sampling techniques for molecular simulations [37,38] have made available the tools for the exploration of large conformational changes at the atomistic level [39][40][41]. In the case of metalloproteins, the use of accelerated sampling techniques requires the use of ad hoc designed force field parameters for the metal ions, able to reproduce structural, thermodynamic, and kinetic observables [42].…”
Section: Discussionmentioning
confidence: 99%